Syntactic analysis of English pop song lyrics on youtube: A linguistic exploration - Romnick P. Vinuya; Angelhen Mae C. Marucut; Rodolfo P. Dizon Jr. (Journal of Education, Social & Communication Studies, 2026)
This study analyzes the syntactic arrangements and punctuation usage in English pop song lyrics on YouTube, focusing on how sentence structures and punctuation marks contribute to the meaning and interpretation of song lyrics. Employing a descriptive qualitative method and Systemic Functional Linguistics as the analytical framework, the study examines 10 pop songs with high audience engagement between 2020 and 2025. Findings reveal various sentence types mainly declarative with frequent grammatical deviations such as double negatives and subject-verb disagreements that serve stylistic functions. Punctuation is shown to play a critical role in shaping tone, rhythm, and clarity, while the interpersonal and ideational aspects reflect informal, playful expression and themes of love and personal growth. The study concludes that increased awareness of syntactic and punctuation norms could enhance lyric clarity, and recommends the use of song lyrics in language learning contexts. Future research may explore further syntactic and linguistic features in popular music. This research contributes to understanding the linguistic strategies employed in contemporary music lyrics and their communicative power.